Advances in Echo Imaging Using Contrast Enhancement - Nanda, Navin C.; Schlief, Reinhard; Goldberg, Barry B. (Springer Netherlands, 1997)
The first edition of this definitive text ran to 24 chapters. The second edition, reflecting the explosive growth of interest in echo-enhancement, contains 44. The first section deals with some of the most important emerging issues and technologies and covers harmonic imaging, the use of echo-enhancers to provide quantitative information, and the application of enhanced power Doppler to tissue imaging. The second, on contrast echocardiography, explores the use of echo-enhancement during transesophageal imaging. One chapter describes the use of contrast-enhancement transesophageal imaging to determine coronary flow reserve and another gives a detailed account of the application of the technique to the evaluation of left ventricular function. Other authors describe the intraoperative use of contrast echocardiography and discuss the potential of myocardial contrast echocardiography to replace thallium scintigraphy. Another chapter covers the emerging technique of transient response imaging and its role in the assessment of myocardial perfusion, and two chapters are devoted to three-dimensional contrast echocardiographic assessment of myocardial perfusion. Use of echo-enhancement in the evaluation of peripheral circulation is discussed in chapters on carotid and peripheral arterial flow imaging and others that describe renal and hepatic vascular imaging. The newer applications of echo-enhancement outside the cardiovascular system are described in three chapters devoted to the visualization of tumour vasculature. The final chapters look to the future and cover the imaging of intramyocardial vasculature, the development of site-specific agents and the emergence of the new acoustically active agents
Keywords: Ultrasound; Diagnosis, Ultrasonic; Ultraschallkardiografie; Aufsatzsammlung